2019
DOI: 10.1080/14737140.2019.1642109
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the link between diabetes and pancreatic cancer

Abstract: Introduction: Epidemiological studies indicate an association between type 2 diabetes and pancreatic cancer but the complex and multidirectional relationship between them remains unclear. Areas covered: We summarized epidemiological evidence on diabetes and pancreatic cancer exploring the time-risk relationship. We described mechanisms linking long-standing diabetes to pancreatic cancer. We discussed pancreatic cancer-associated diabetes and its implication in the early detection of pancreatic cancer. Expert o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 88 publications
1
20
0
Order By: Relevance
“…Based on the biological complexity of PC, a bidirectional relationship between DM and PC has been identified, since 2005 [35]. As stated earlier, many recent studies have concluded that DM is both a consequence, as well as, a cause for PC [36]. Overall, studies report that most patients with pancreatic cancer have hyperglycemia or diabetes.…”
Section: The Pancreas and Insulinmentioning
confidence: 97%
See 3 more Smart Citations
“…Based on the biological complexity of PC, a bidirectional relationship between DM and PC has been identified, since 2005 [35]. As stated earlier, many recent studies have concluded that DM is both a consequence, as well as, a cause for PC [36]. Overall, studies report that most patients with pancreatic cancer have hyperglycemia or diabetes.…”
Section: The Pancreas and Insulinmentioning
confidence: 97%
“…The connection between PC and DM has been explained by several translational, clinical and epidemiological studies. The largest original epidemiological studies showed clearly that new-onset hyperglycemia and DM are early signs of PC [28,30,35,36]. As PC is usually diagnosed at the late stage of the disease, given the overall 5 year survival rate is less than 5%, the duration of survival actually depends on the histological TNM grading of tumor and the resection ratio [29,37,38].…”
Section: The Pancreas and Insulinmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity and high caloric intake linked co-morbidities like type 2 diabetes (T2D) have been attributed as being risk factors for a number of cancers including pancreatic cancer [1,2]. Apart from being considered as one of the risk factors for pancreatic cancer, late onset of diabetes is now being evaluated as a potential early biomarker for pancreatic cancer [3][4][5]. Studies have shown that pancreatic cancer patients with T2D have poor survival statistics [6].…”
Section: Introductionmentioning
confidence: 99%